The Snow Empress - Laura Joh Rowland
Japan, 1699: On a moonlit night on the northern frontier island of Ezogashima, a woman is running through the forest when an arrow strikes her dead. Meanwhile, in the city of Edo, the young son of Sano Ichiro, the samurai detective who has risen to power in the shogun$1 (Bs court, vanishes during a moon-watching festival. When one of Sano$1 (Bs political rivals hints that the boy was kidnapped$1 (Band may be in Ezogashima$1 (Bhe and his wife, Reiko, begin a desperate journey to find their son$1! =(Bonly to discover that the local ruler, Lord Matsumae, is holding the entire province hostage for another The murder of his mistress. So Sano strikes a He will solve the mistress$1 (Bs murder if Matsumae will free the hostages and return his son. Soon, however, Sano and Reiko find themselves caught up in a dangerous scheme that includes clan warfare, bitter jealousy, and murderous betrayal as they race to unravel the mystery of THE SNOW EMPRESSs